The Role Of Tourism Enterprises In The Application Of Bali Cultural Values In Hotels In Badung - Made Arya Astina; I Gusti Ayu Eka Suwintari (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
This research on tourism human resources is entitled The role of tourism business in the application of Balinese cultural values to hotels in Badung. Badung Regency was chosen as the research location with several considerations: 1) Badung is the district with the fastest tourism growth in Bali, 2) The growth in the number of hotels in this area is followed by a growth in the number of hotel employees, 3) The culture of hotel employees in Badung Regency needs to be maintained. Considered that the province of Bali relies on the tourism sector for its main regional income, this research is important because the application of local wisdom to tourism human resources is an important component in a service. This study produces information about the role of tourism/hotel business actors in the application of local wisdom values in hotels in Badung Regency. This research includes descriptive research by utilizing a qualitative approach. In this study, the authors explore data and information about the role of the tourism industry in implementing local cultural values in running their business. The stages carried out in this study 1) Identify Balinese cultural values applied by tourism actors (hotel employees) in Badung, 2) identify the role of tourism business people in the application of local culture as a strategy to increase the superior value of tourism business services.